PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP E-LOYALTY DENGAN E-SATISFACTION SEBAGAI VARIABEL INTERVENING (STUDI PADA PELANGGAN SORABEL DI BANDUNG) - Sekar Sedyaning Kasih; Nadya Novandriani Karina Moeliono (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to determine the effect of e-service quality dan e-trust towards e-loyalty as e-satisfaction as intervening variable on Sorabel consumers in Bandung. The type of the study used are descriptive and casual. The sampling of this research uses non  probability sampling method aside from 100 people. The research is quantitative and uses descriptive analysis technique and path analysis technique. Questionnaire   be measured use Likerts Scale. Data processing was performed using SPSS 25s . The results of the descriptive analysis showed that the e-service quality, e-trust, e-satisfaction and e-loyalty variables were in the good category. The results of the study prove that e-service quality and e-trust have an influence on e-satisfaction and e-service quality and e-trust have influence on e-loyalty with e-satisfaction as an intervening variable.